1878 Iowa Acts 108 - (:unkn) unknown (My University, 1878)
Military Code of Iowa, chap. 125, § 1: Included all able-bodied male citizens between the ages of eighteen and forty-five years as party of the militia
Keywords: ARMED FORCES